PROSES REGISTRASI PADA ACARA INDONESIA INTERNATIONAL SUSTAINABILITY FORUM (IISF) 2024 - Amelia Diah Puspita Puspita; Sudarno Sudarno; Noni Noerkaisar; Karbala Madania (Program Studi MICE, Jurusan Administrasi Niaga, Politeknik Negeri Jakarta, 2026)
This study examines the multifaceted registration process implemented for the Indonesia International Sustainability Forum (IISF) 2024, assessing its efficiency and impact on overall event management. As a nation with significant natural resources, Indonesia’s commitment to sustainable development is paramount, making IISF a vital platform for advancing green initiatives. The research adopts a qualitative and comparative analysis methodology, drawing insights from direct observation, detailed meeting minutes, and a comprehensive case study conducted during a six-month internship at Kadin Indonesia. Key findings reveal a comprehensive online pre-registration, a stringent participant verification process guided by a specific matrix, and a streamlined re-registration procedure using QR codes and RFID technology. The paper also identifies and discusses specific challenges encountered, such as data accuracy and managing diverse participant expectations, alongside the practical solutions implemented. This research underscores the critical role of an effective and user-friendly registration system in the successful execution of large-scale international MICE (Meetings, Incentives, Conventions, and Exhibitions) events, offering valuable lessons and best practices for future event planning and contributing to the body of knowledge in professional event management.